Pola Belajar Mahasiswa Pekerja Part time: Studi di Universitas Islam Negeri Sumatera Utara Jurusan PAI - Arlina, Arlina; Siti Aisyah; Alya Fadhluna Zamzam; Nevi Rizkia Yusuf; Aslamiah Abda Daulay; Abdi Ardiansyah Sihotang (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to examine the learning patterns of part-time student students studying at the State Islamic University of North Sumatra majoring in PAI. This study used descriptive qualitative method. Data collection techniques were used by means of observation, interviews and documentation. The results of the research show that students who work part time at UINSU majoring in PAI predominantly choose independent study patterns because of the flexibility of time that fits their busy schedules. The second most popular learning pattern is peer tutoring. Meanwhile, only a small number of students choose discussion or group learning patterns. Thus, from the results of this research it can be concluded that part-time working students at the State University of North Sumatra, Department of Islamic Religious Education, predominantly choose independent study patterns.